Predictive Artificial Intelligence Tools in the U.S. Criminal Trial : Reflections on Technology and Justice - Ilhan, Mina Ayşe (Université Côte d'Azur, 2025)
Under the aegis of efficiency and neutrality, algorithmic risk-assessment tools have been rapidly inserted into the realm of pretrial justice, promising scientific and objective prediction where presumption of innocence and scarce resources are pitted against each other. Their sprawl has been uneven and confined to looser pretrial rules than would govern similar proof at trial. These systems translate miscellaneous data into scores of “risk,” inviting courts to act on what might happen rather than on what has been proven, within a process already plagued by plea bargaining, racial disparity, and institutional asymmetry. This thesis argues that such tools do not merely constitute information about the defendant; they reorder what counts as usable knowledge and who is treated as a credible knower at the weakest stage of a criminal process. The thesis lays out how scores interact with judicial decision-making; how ostensibly neutral inputs (criminal history, prior contacts, residence, employment) can re-encode social disadvantage; and how opacity and trade-secret claims frustrate fundamental rights such as due process. The doctrinal analysis clarifies the boundary between regulation and punishment under United States v. Salerno, the demands of proportionality, and the significance of the presumption of innocence when decisions are predictive. A brief technical account explains why claims of “explainability” often exceed what such models can reliably demonstrate for legal purposes, but the core argument is juridical: claims of legitimacy must be substantiated by enforceable safeguards; falling short of that, systems described as ‘explainable' or ‘fair' remain as fancy adjectives. The thesis contends that the safeguards that govern the trial must be applied earlier in the criminal process, where liberty is already fragile. Accordingly, the thesis argues for invoking evidentiary rules early on: demonstrating reliability of the tools; reasoned judicial decisions that explain how any score was weighed against case-specific facts; meaningful opportunities for defence challenge; and, where appropriate, access to independent expertise to translate model outputs without displacing judicial authorship. The researcher is of the opinion that these emphases are necessary so that pretrial decisions remain individualised and proportionate and detention retains its status as an exceptional, non-punitive measure. Finally, it defends doubt as a juridical virtue, a disciplined moment of pause that reins in the allure of algorithmic certainty and reasserts judicial responsibility, so that the presumption of innocence and liberty remains the rule even in a predictive age. Sous l'égide de l'efficacité et de la neutralité, les outils algorithmiques d'évaluation du risque ont été rapidement introduits dans le domaine de la justice pré-procès, promettant une prédiction scientifique et objective là où la présomption d'innocence et la rareté des ressources se trouvent mises en tension. Leur déploiement a été inégal et s'est inscrit dans des règles pré-procès plus souples que celles qui régiraient des éléments de preuve similaires au stade du procès. Ces systèmes traduisent des données hétérogènes en scores de « risque », invitant les juridictions à agir en fonction de ce qui pourrait advenir plutôt que de ce qui a été prouvé, au sein d'un processus déjà marqué par le plaider-coupable, les disparités raciales et les asymétries institutionnelles. La présente thèse soutient que de tels outils ne constituent pas seulement une information relative au prévenu ; ils réorganisent ce qui compte comme connaissance mobilisable et déterminent qui est traité comme un sujet crédible de savoir au stade le plus fragile de la procédure pénale. Elle expose la manière dont les scores interagissent avec la prise de décision judiciaire ; comment des variables présentées comme neutres (antécédents judiciaires, contacts antérieurs avec la police, résidence, emploi) peuvent réencoder des désavantages sociaux ; et comment l'opacité ainsi que les revendications de secret commercial entravent des droits fondamentaux tels que le droit à une procédure régulière. L'analyse doctrinale précise la frontière entre régulation et punition au regard de l'arrêt United States v. Salerno, les exigences de proportionnalité et la portée de la présomption d'innocence lorsque les décisions sont de nature prédictive. Un bref exposé technique explique pourquoi les prétentions à « l'explicabilité » excèdent souvent ce que ces modèles peuvent démontrer de manière fiable à des fins juridiques, mais l'argument central demeure juridique : les revendications de légitimité doivent être étayées par des garanties effectives ; à défaut, les systèmes qualifiés d'« explicables » ou d'« équitables » ne demeurent que des adjectifs séduisants. La thèse soutient que les garanties gouvernant le procès doivent être appliquées plus en amont dans le processus pénal, là où la liberté est déjà fragile. En conséquence, elle plaide pour une mobilisation précoce des règles de preuve : démonstration de la fiabilité des outils ; décisions judiciaires motivées expliquant la manière dont tout score a été mis en balance avec les faits propres à l'affaire ; possibilités effectives de contestation par la défense ; et, le cas échéant, accès à une expertise indépendante permettant de traduire les résultats des modèles sans se substituer à l'autorité judiciaire. La chercheuse estime que ces exigences sont nécessaires afin que les décisions pré-procès demeurent individualisées et proportionnées, et que la détention conserve son caractère exceptionnel et non punitif. Enfin, la thèse défend le doute comme une vertu juridique, moment discipliné de suspension qui tempère l'attrait de la certitude algorithmique et réaffirme la responsabilité judiciaire, afin que la présomption d'innocence et la liberté demeurent la règle, y compris à l'ère prédictive.
Issue: 2025COAZ0023
Keywords: Algorithmes; Algorithmes predictifs; Algorithms; Criminal Justice; Intelligence artificielle en droit; Justice criminelle; Justice prédictive; Procès; Risk assessment tools; États-Unis

The commercial sexual exploitation of children perpetrated by the private sector: can international law be improved? - Hecht, Mark (Université de Sherbrooke, 2023)
International law is a robust system designed to unite world governments in an effort to, inter alia, cease human rights violations and hold those who commit them accountable. As it currently stands, and by its own design, the international human rights legal regime focuses on and applies only to state actors, meaning that violations committed by non-state actors, such as multinational corporations (MNCs), are seemingly conducted with impunity inside this space. Multinational corporations are powerful international players that have undoubtably fostered a significant role in reducing global barriers. By their very nature, they are far more mobile than states, allowing them to evade domestic power and regulatory schemes by detaching from their home state and relocating to a host state with weaker oversight and/or enforcement powers. Simply stated: even though MNCs have better financing, heightened mobility, and a disproportionate amount of influence when compared to world states, they operate with less global accountability. Commercial sexual exploitation of children (CSEC) is a fundamental violation of children’s rights. It consists of sexual abuse by the adult and remuneration in cash or kind to the child or a third person or persons. The child is treated as a sexual object and as a commercial object. Multinational corporations have been implicated in CSEC through acts of omission and commission. And despite the fact that much international law has been drafted to protect children around the world from CSEC—most notably the United Nations Convention on the Rights of the Child and its Optional Protocols—the numbers of children who have been emotionally and physically harmed by and through MNC conduct has only increased in the past decade. There have been numerous efforts by international organizations to address the challenges when regulating and monitoring human rights violations by MNCs. States, civil society organizations, and the private sector itself have also attempted to address these human rights violations through domestic law, modifying international law principles, and with civil regulation. Obstacles exist in the effectiveness of each of these approaches, leaving children at risk with no single effective strategy to combat and address rights violations by MNCs. The dissertation conducts a review of the current landscape of child law, through the lens of corporate accountability for CSEC. Then, it suggests a new alternative, putting forward an international solution to an international problem.
Keywords: Commercial sexual exploitation of children; Convention on the rights of the child; Corporate Social Responsibility; International child law

Botswana’s Anti-Money Laundering and Combating the Financing of Terrorism Regime - Tshiamo-Kgati, Kuda (University of Pretoria, 2021)
Money laundering, the financing of terrorism and proliferation financing continue to be serious threats to the stability of the international financial system. The international community therefore has prioritised the fight against these activities. For example, international bodies such as the Financial Action Task Force (FATF) and others have developed standards and recommendations against which countries and organisations are measured in this regard. Against this background, this thesis investigates to what extent Botswana’s legislative framework regarding money laundering, terrorism financing and other illicit financial flows complies with international standards, especially the FATF Recommendations. The study sets the scene by defining and describing money laundering, financing of terrorism and proliferation financing, after which the current statutory framework in Botswana is discussed in detail. After subsequently setting out the various global and regional (specifically African) initiatives in the fight against money laundering and other financial crimes, the current state of affairs in Botswana is benchmarked against both the South African framework as well as the FATF Recommendations. The investigation is limited to a technical assessment (doctrinal analysis) of Botswana law to determine the current compliance (or lack thereof) of the country’s statutory provisions and to make recommendations regarding how the framework can be improved. It is difficult for some countries, especially African countries like Botswana, to comply fully with the FATF Recommendations, since compliance can be expensive and dependent on high levels of expertise on the part of the relevant authorities. Therefore, such more vulnerable countries tend to face a higher risk of being used as conduits for money laundering and related activities. Despite these and other challenges, Botswana has gone to great lengths to re-assess and improve its anti-money laundering and combating the financing of terrorism (AML/CFT) legislation with a view to move towards full compliance with the FATF Recommendations. Nevertheless, the evaluation indicates that there are some remaining shortcomings in Botswana’s legislation. Consequently, the thesis concludes by proffering certain recommendations towards ensuring that Botswana’s AML/CFT legislation is rendered fully compliant with the FATF Recommendations.
URI: https://repository.up.ac.za/handle/2263/82675
Keywords: AML/CFT; Anti-money laundering; Botswana; Financement du terrorisme; Financial law; LBC/FT; Lutte contre blanchiment de capitaux; Money laundering

Improving international investment law’s treatment of (anti-)corruption: Towards a more balanced approach - Yan, Yueming (McGill University, 2021)
In recent years, investment arbitration tribunals are increasingly confronted with allegations of corruption, mostly invoked by host States as a defense to investors’ claims. After an affirmative finding of an alleged corrupt act between the investor and a public official of the host State in the establishment or conduct of the investment, tribunals have adopted a binary approach to the issue – if they uphold allegations of corruption, they completely dismiss the investor’s submissions. This binary approach has resulted in an asymmetry of liability for the two parties to a corrupt act (i.e., investors and host States/host State officials), failing to take into account the inherent bilateralism of corruption and the fact that domestic laws and international norms have outlawed both the act of offering and of accepting bribes. In particular, public officials’ free participation in a corrupt act to advance investments is attributable to the host State and requires State responsibility under international law. Moreover, the increasingly prevalent practice of inserting anti-corruption provisions in investment treaties has reinforced this lop-sided feature, as well as offering only weak effectiveness in terms of deterring corruption. After a careful examination of the treatment of corruption issues in investment arbitration and investment treaties, this thesis proposes a paradigm shift from the current asymmetric approach to a more balanced approach. It calls on investment tribunals to take a dual-track approach that investigates both corruption and investors’ claims, and ensures that each party assumes responsibility for its own misconduct. It also proposes that treaty drafters include anti-corruption provisions that impose strong obligations of anti-corruption on both sides of corruption (i.e., investors and host States) rather than merely on a single party to it
https://escholarship.mcgill.ca/concern/theses/5q47rt984
Keywords: Anti-Corruption Law; Investment arbitration; Investment treaty; Investments

Combating corruption in public procurement in developing countries : a legal analysis - Mugadza, W. T. (North-West University, 2018)
This study was motivated by the quest to find new innovative and practical ways of combating public procurement corruption in developing countries to complement the existing measures. This was achieved by comparing three jurisdictions, Hong Kong-China, Botswana and South Africa. The focus was on how each jurisdiction uses the following four measures to curb public procurement corruption: criminal measures; administrative measures; institutional measures and civil activism measures. It was established that Hong Kong uses what this study has classified as the traditional approach of combating public procurement corruption. The traditional approach is characterised by the use of a separate procurement legal framework and a separate corruption legal framework to curb public procurement corruption. Its strengths are in the strict enforcement of criminal measures that are anchored on a robust legal framework, a clear anti-corruption strategy, an independent anti-corruption agency (institutional measure), effective internal oversight and a strong political will. However, the following weaknesses of the traditional approach were identified: over reliance on criminal measures; excessive dependence on one enforcement institution; it neglects the development of administrative measures and has weak civil activism measures. It was established that Botswana uses what this study has classified as the classical approach of combating public procurement corruption. The classical approach is characterised by a procurement legal framework that incorporates very minimum anti-corruption provisions. The anti-corruption provisions in the procurement legislation are enforced by an external institution (the DCEC in the case of Botswana) which relies heavily on the criminal measures. Its strengths are the following: a strong legal framework which provides for a clear anti-corruption strategy; it has anti-corruption units in each Ministry and it has a dedicated Corruption Court. However, the classical approach has the following weaknesses: the anti-corruption agency is not adequately independent as it under the control of the executive (the President in the case of Botswana); lacks effective internal oversight mechanisms; weak political will; neglects the development of administrative measures and civil activism measures are almost non-existent save for the media. It was established that South Africa uses what this study has classified as the traditional cum silo approach of combating public procurement corruption. The traditional cum approach is characterised by multiple procurement legislation which has certain but minimum anti-corruption provisions and a separate corruption legal framework. Multiple anti-corruption agencies are prone to political interference which renders them ineffective and unfit for purpose. Its strength is in the promotion and protection of civil activism measures (right to access information, right to freedom of speech and legal protection of whistle-blowers). Notable weaknesses of the traditional cum silo approach are: the poor enforcement of criminal measures; there is no lead anti-corruption agency that spearheads and coordinates all cases of public procurement corruption; there is no clear anti-corruption strategy; the administrative measures such as debarment are poorly enforced; it has multiple anti-corruption institutions that lack focus and professionalism which results in political manipulation. The thesis concluded by suggesting a new approach, the contemporary approach to combating public procurement corruption which entails the enactment of a single procurement legislation (model law) the Public Procurement and Combating of Public Procurement Corruption Act (hereafter PPCPPC). The contemporary approach advocates for the regulation of public procurement and the combating of public procurement corruption in one legislation. This legislation (PPCPPC) takes into account, the current demands for public procurement as well as future developments of public procurement. These include but are not limited to self-cleaning, cyber-crime and public procurement corruption as well as the role of foreign convictions for debarment purposes. The envisaged PPCPPC will in addition to regulating public procurement, encompass the best criminal measures, administrative measures, institutional measures and civil activism measures. In addition, the contemporary approach through the PPCPPC proposes two new innovations: the corruption clearance certificate and a mandatory anti-corruption clause in all government contracts.
Keywords: Accountability; Administrative measures; Anti-corruption clause; Botswana; Civil activism measures; Classical approach; Combating corruption; Competitiveness; Contemporary approach; Corruption clearance; Criminal measures; Debarment; Equality; Fairness; Hong Kong; Institutional measures; Integrity; Procurement principles; Public procurement; South Africa; Traditional approach; Transparency; Value for money

A South African perspective on the meaning of "beneficial ownership" in Article 10 of the OECD Model Tax Convention on Income and Capital in the context of conduit company treaty shopping - Jansen van Rensburg, Enelia Cornelia (University of Pretoria, 2018)
The use of conduit company treaty shopping structures is often regarded as an impermissible erosion of a country’s tax base. For a developing country, such as South Africa, the protection of its tax base is an important policy consideration. Arguably, one way of combatting conduit company treaty shopping structures is by including in a country’s double taxation agreements the beneficial ownership requirement set out in Article 10(2) of the OECD MTC. The study examines how a South African court would interpret this requirement in provisions in South African double taxation agreements in the context of conduit company treaty shopping involving conduit companies receiving dividends. The study firstly considers whether the beneficial ownership requirement can be regarded as an anti-avoidance rule aimed at combatting conduit company treaty shopping falling outside agents and nominee scenarios. It further considers whether the term “beneficial owner” should have a legal or economic meaning. It explores the meanings given to this term by scholars and foreign courts and the OECD in its Commentaries to the OECD MTC. The study also considers the application of the rules of interpretation contained in the Vienna Convention on the Law of Treaties when giving meaning to this term. Lastly, the study considers whether the term should have the meaning assigned to it under the domestic law of a treaty country, or under international tax law. As part of this enquiry, the meanings of the expression “beneficial owner” in South African case law and legislation are explored.
https://repository.up.ac.za/handle/2263/65660
Keywords: Beneficial ownership; Conduit company treaty shopping; OECD; OECD Model Tax Convention; Société écran; South Africa

Understanding fiduciary duties: conflict of interest and proper exercise of judgment in private law - Valsan, Remus (McGill University, 2012)
This dissertation analyses the content and justification of the notion of fiduciary duties in private law relations. The thesis promotes the following understanding of fiduciary duties: in a legal relation where one party undertakes to act in the interests of another, and acquires decision-making authority over the other's interests, such party undertakes a core duty to exercise his best judgement in the other's interests. The core judgement duty requires a fiduciary to exercise judgement based on relevant considerations. While what constitutes a relevant consideration can be determined objectively, the weight to be ascribed to each relevant factor is left at the fiduciary's subjective appreciation.Due to the existence of this core duty, the law imposes a set of proscriptive duties. The proscriptive duties require a fiduciary to manage situations of conflict of interest. Their purpose is prophylactic: they aim to prevent self-interest (or another duty to exercise proper judgement) from affecting the reliability of fiduciary's judgement in a conscious or subconscious way. The proscriptive duties protect the core duty to exercise judgement and, as a result, the beneficiary's right to a proper exercise of judgement by the fiduciary.
https://escholarship.mcgill.ca/concern/theses/wd376141g
Keywords: Conflict of interest; Fiduciary duties; Judgment; Private law